Report of the Wintering Party of the Japanese Antarctic Research Expedition in 1975-1976 - Takao HOSHIAI (Antarctic Record, 1978)
The 16th wintering party of the Japanese Antarctic Research Expedition (1975-1976) consisting of thirty members was in charge of research activities at Syowa Station for the period from February 1975 to January 1976. The research programes comprised many items in various disciplines, namely, aurora, geomagnetism, ionosphere, meteorology, oceanography, seismology, cartography, geology, geomorphology, geochemistry, biology and medical science. The emphasis was laid on the last six disciplines. Three field parties were dispatched for geological, geomorphological, and biological surveys of the ice-free areas along the Soya Coast in May, August and October 1975. An oversnow traverse for geological and geodesical survey in the Yamato Mountains area was conducted from November 1975 to January 1976. Search and collection of meteorites was attempted and 307 meteorites including two iron meteorites were discovered around the Yamato Mountains. Samplings of snow for chemical analysis were carried out at Mizuho Camp (now Mizuho Station) in September and also en route between Syowa and Mizuho in January, May and October 1975. The single-engine monoplane, Cessna A185F was operated for aerophotographical survey in the areas covering the Prince Olav Coast, the Soya Coast and the coastal area between 30° and 35°E; the Yamato Mountains area and the Belgica Mountains area. By the plane, an Emperor Penguin rookery was discovered on the sea ice of the east coast of the Liiser-Larsen Peninsula and population census of Adelie Penguin and Weddell seal was also carried out.